Introduction: Mimetic Governmentality, Colonialism, and the State - Ladwig, Patrice (2020)
Late Western colonialism often relied on the practice of imitating indigenous forms of rule in order to maintain power; conversely, indigenous polities could imitate Western sociopolitical forms to their own benefit. Drawing on historical ethnographic studies of colonialism in Asia and Africa, States of Imitation examines how the colonial state attempted to administer, control, and integrate its indigenous subjects through mimetic governmentality, as well the ways indigenous states adopted these imitative practices to establish reciprocal ties with, or to resist the presence of, the colonial state.